PENGARUH KOMPRES BAWANG MERAH TERHADAP PENURUNAN SUHU TUBUH PADA ANAK DENGAN HIPERTERMIA - Juniah; Edita Revine Siahaan (Jurnal Keperawatan Bunda Delima, 2022)
THE EFFECT OF ONION COMPRESS ON REDUCING BODY TEMPERATURE IN CHILDREN WITH HYPERTERMIA ABSTRACT Child is someone who is not yet 18 years old (eighteen) years, including children who are under protection of children since the child is in the womb until the age of 18 years. Hyperthermia is a condition where there is an increase in body temperature above the normal body range due to the body's inability to increase the ability to compete in heat. Complications of fever that can occur, namely the onset of dehydration, hallucinations, convulsions non-pharmacological action to reduce temperature is a red onion compress. Onion compress is an action taken on clients who have increased body temperature who need help to reduce body temperature in children with fever. The purpose of this literature review is to describe the effect of onion compresses on decreasing body temperature in children with hyperthermia. This type of literature review is a literature review study by collecting online journal search results using Google Scientist by searching for 10 articles and then reducing them to 5 articles that match the literature criteria. Data analysis showed that after the action of compressing the onion at 36.00C in children who had hyperthermia. There is a difference in the effectiveness of the onion compress on the problem of hyperthermia in children, which turns out to be more effective in reducing body temperature in children. This literature review describes shallot compresses on decreasing body temperature in children with hyperthermia. Keywords: Children, hyperthermia, onion compress.